2019
DOI: 10.3390/vaccines8010001
|View full text |Cite
|
Sign up to set email alerts
|

Immunization against Hepatitis B Surface Antigen (HBsAg) in a Cohort of Nursing Students Two Decades after Vaccination: Surprising Feedback

Abstract: Health-care students can be exposed to biological risks during university training. The persistence of long-term immunogenicity against hepatitis B virus (HBV) was analyzed in a cohort of nursing students two decades after primary vaccination. A total of 520 students were enrolled at the University of Palermo and were evaluated for levels of anti-HBsAg antibodies. The students were examined during the first year of their Degree Course and were checked two years later. All students with anti-HBsAg <10 mIU/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Studies concerning the assessment of the persistence of protective antibody titers in the pediatric population have shown that 15-50% of responder subjects may have low or non-detectable antibody concentrations after 5-24 years since the vaccination [34][35][36]. The results obtained in the present study are, in this respect, in accordance with the collected data in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Studies concerning the assessment of the persistence of protective antibody titers in the pediatric population have shown that 15-50% of responder subjects may have low or non-detectable antibody concentrations after 5-24 years since the vaccination [34][35][36]. The results obtained in the present study are, in this respect, in accordance with the collected data in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…However, this percentage does not imply a susceptibility status for these subjects: the WHO affirms that even if the anti-HBs titers are not detectable following the immunization series, no booster dose is needed [1][2][3]. This is a consequence of the immune memory widely described for hepatitis B vaccination in the scientific literature [35,38].…”
Section: Discussionmentioning
confidence: 99%
“…The students were evaluated for levels of anti-HBsAg antibodies showing a difference between receiving HBV vaccination at adolescence and at infancy. Vaccinated students at adolescence showed a significant association with an increased possibility of having anti-HBsAg titers ≥ 10 mIU/mL than those who were vaccinated at infancy (69% vs. 31.7%) [137]. But, on the other hand, the vaccine is not effective against an already established infection nor against escape mutants at vaccination.…”
Section: Discussionmentioning
confidence: 85%
“…At the same time, about 30-60% of adults vaccinated against HBV will have anti-HBs concentrations decline to <10 mIU/mL within 9-11 years [20].…”
Section: Discussionmentioning
confidence: 99%